Synthesis and Liquid Crystalline Studies of 2,4-bis(4'-n-nonyloxybenzoyloxy)benzylidene-4''-n-alkoxyaniline - Hamad, Wali M.; Salih, Shalaw K. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
In this paper, a series of new Schiff-bases: 2,4-bis(4’‑n‑nonyloxy -benzoyloxy)benzylidene-4’’-n-alkyloxyaniline (DC9An) were synthesized. The characterization of compounds was achieved through using (ultra violet, infrared, 1H-nuclear magnetic resonance) measurements. This series comprises 10 members differ by the length of n-alkoxy chain (i.e., OCnH2n+1, n=1-10). Their liquid crystalline properties were studied using differential scanning calorimetry and polarizing optical microscopy. The lower series such as n=1-3 are purely nematogenic liquid crystals, but the other means (n=4-7) have nematic and smectic phases (SmC and SmA). The higher members (n=8-10) are purely smectogenic liquid crystals.